The advertisement call of Stumpffia be Köhler, Vences, D’Cruze & Glaw, 2010 (Anura: Microhylidae: Cophylinae) - Lattenkamp, Ella Z.; Mandák, Martin; Scherz, Mark D. (Zootaxa, 2016)
We describe the calls of Stumpffia be Köhler, Vences, D’Cruze & Glaw, 2010. This is the first call description made for a species belonging to the large-bodied northern Madagascan radiation of Stumpffia Boettger, 1881. Stumpffia is a genus of small ( 9–28 mm) microhylid frogs in the Madagascar-endemic subfamily Cophylinae Cope. Little is known about their reproductive strategies. Most species are assumed to lay their eggs in foam nests in the leaf litter of Madagascar’s humid and semi-humid forests (Glaw & Vences 1994; Klages et al. 2013). They exhibit some degree of parental care, with the males guarding the nest after eggs are laid (Klages et al. 2013). The bioacoustic repertoire of these frogs is thought to be limited, and there are two distinct call structures known for the genus: the advertisement call of the type species, S. psologlossa Boettger, 1881, is apparently unique in being a trill of notes repeated in short succession. All other species from which calls are known emit single, whistling or chirping notes (Vences & Glaw 1991; Vences et al. 2006).